Сучасні підходи до проблеми автоматизації теплообмінників - Ладанюк, Анатолій Петрович; Кроніковський, Дмитро Олегович (My University, 2012)
В статті розглянуто практичні проблеми автоматизації теплообмінників. Наведено найпоширеніші мотиваційні причини необхідності використання сучасних методик діагностики функціонування теплообмінників. Чітко виокремлено поломки при функціонуванні теплообмінників. Розглянуто варіанти виявлення та попередження відхилення функціонування від заданого (оптимального) режиму. Запропоновано використання комбінації методів параметричної ідентифікації та контрольних карт Шухарта, причому обґрунтовано та наведено схему побудови та функціонування даного алгоритму. Серед можливих варіантів комбінацій точок контрольних карт Шухарта ідентифіковано ситуаційну відповідність роботи теплообмінника та можливість настання поломки. Наведено методику виявлення за допомогою параметричної ідентифікації товщини відкладень на поверхні трубок 8, середню швидкість їх росту ю, час Ь досягнення небезпечної величини відкладень та ступінь засмічення трубок В. In modern technological objects significant role play heat processes. Heat transfer between the coolant separated by a solid wall, contains all known methods of heat transfer. Knowledge of the mechanism of flow, heat transfer and skills, in particular, reliably calculate heat transfer and hydraulic losses is necessary for the design of power devices and to develop a reliable system of automatic control. Therefore, research of heat transfer and hydrodynamics in heat exchangers, the development of methods of calculation, diagnostics and au tomation represent actual engineering practice nowadays. Widespread use of heat exchangers of various designs and purposes puts additional conditions on the quality of automation systems, in particular with a view to saving energy.The article deals with practical problems of automation of heat exchangers. Most common reason given motivational need for modern methods of functional diagnostics of heat exchangers Clearly distinguished damage in operation of the heat exchangers. We. examined the detection and prevention of deviation from the set operation (optimal) functionality. Proposed using a combination of parametric identification and control Shuharts cards. Was described reason and structure of functioning of the algorithm. Among the possible choices of points combinations Shuharts cards identified situational compliance of the heat exchanger and the possibility of breakage. The method show the way of parametrical identification of the thickness of deposits on the surface of the tubes, the average rate of growth, rising of a dangerous amount of deposits and the degree of clogging pipes.
Keywords: тренди; теплообмінник; автоматизація; trends; heat exchanger; automation; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка